Effect of Citrullus lanatus seed oil on xerosis in leprosy patients - Puteri Wulandari; Syahril Rahmat Lubis; Deryne Anggia Paramita (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2022)
Xerosis in leprosy patients may result from defects in sweat gland function.Red watermelon (Citrullus lanatus) seed oil a lot of contains linoleic acid,which can hydrate the skin and reduce trans-epidermal water loss (TEWL).This study aimed to evaluate the effect of C. lanatus seed oil administrationin leprosy patients with xerosis. It was a clinical study with one group pretestposttest control group design involving 30 leprosy patients with xerosis at theDepartment of Dermatology and Venereology, Dr. Pirngadi Medan Hospital, thePolyclinic of Dermatology and Venerology, Universitas Sumatera Utara Hospitaland the Department of Dermatology and Venerology, H. Adam Malik GeneralHospital, Medan, Indonesia. Patients were asked to topically administration of2 mL C. lanatus seed oil to the right and left legs for two times daily for 4 weeks.Specified symptom sum score (SRRC) and skin capacitance (SCap) were thenmeasured before the intervention at the first visit (week 0), week 2, and week 4.A significantly different on SRRC and SCap of the leprosy patients was observedon the 2nd and 4th week after C. lanatus oil administration compared to week 0(p<0.001). No side effects of erythema, blistering, and burning were observed.However, a mild degree itching was observed in 2 (6.7%) patients. Majority ofleprosy patients feel good satisfaction (83.4%), followed by a moderate (13.3%)and a low satisfaction (3.3%). In conclusion, topically administration of redwatermelon (C. lanatus) seed oil can reduce the xerosis degree in leprosypatients as indicated by the decrease of SRRC and the increase of SCap. Theseed oil is well tolerated and gives a good satisfaction on the patients.